Rigorous modeling of CO2 absorption and chemisorption: The influence of bubble coalescence and breakage. (1st December 2015) - Gruber, Michael C.; Radl, Stefan; Khinast, Johannes G.
Abstract: In this study, the impact of bubble breakage and coalescence (B&C) on the mass transfer and on the temporal evolution of species concentration during absorption and chemisorption is investigated. For this purpose, the CO2 absorption in water and the CO2 chemisorption in NaOH solutions of various initial pH serve as model cases. A three-dimensional Euler–Lagrange algorithm is used for the handling of the gaseous and the liquid phase in a model (simulation) of a laboratory-scale bubble column. The algorithm accurately forecasts the mean and fluctuating liquid velocities and predicts the bubble size distribution reasonably well. The results show that B&C critically impact mass transfer, liquid phase mixing, as well as reaction rates in systems with low to moderately large pH. In contrast, for extremely high pH values, shrinkage of bubbles becomes the dominating phenomenon. This is because bubble shrinkage leads to small bubbles, low gas hold-up, as well as little liquid phase agitation in the upper part of the reactor. Consequently, the relevance of B&C events decreases gradually with increasing pH. A plot of the results as function of the overall pH illustrates that a regime change occurs close to pH 12.5. This transition is caused by a dramatic reduction of the gas hold-up, leading to a significant reduction of liquid-phase agitation. Graphical abstract: Highlights: Euler–Lagrange simulation of bubble break-up and coalescence (B&C) in bubble column. CO2 absorption in water and CO2 chemisorption in NaOH solutions with pH 12.0–14.0. Moderate pH: B&C has impact on mass transfer, liquid mixing and reaction rates. High pH: Shrinkage of bubbles becomes the dominating phenomenon. Regime change occurs at pH 12.5: Reduction of gas hold-up and liquid-phase agitation.